Colorectal Cancer from an Ayurvedic Perspective: Integrative Review (International Journal of Ayurveda and Pharma Research, 2025)
Colorectal cancer (CRC) is a leading cause of cancer-related morbidity and mortality globally, with rising incidence in developing populations, including India. While conventional oncology focuses on genetic, dietary, lifestyle, and environmental risk factors, Ayurveda speculates abnormal growths such as tumors under Arbuda and Granthi, assigning their pathogenesis to imbalances in Doshas, Dhatus, Srotas, and impaired Agni. This description review integrates biomedical and Ayurvedic perspectives on CRC, examining disease burden, risk factors, dietary influences, and potential adjunctive therapies. Evidence from hospital-based case-control studies indicate associations between certain dietary patterns (e.g., excessive consumption of pungent foods and curd) and increased CRC risk, associating with Ayurvedic concepts of Ushna, Ruksha, Kleda, and Srota avarodha. Preclinical and in-silico studies suggest that Ayurvedic Medicines, including Curcumin, Triphala, and Glycyrrhiza glabra, may modulate tumor pathways, though clinical evidence remains inadequate. Integrative preventive strategies emphasizing dietary-lifestyle modifications, maintenance of Agni, Srotas, and use of supportive herbs show promise in CRC risk reduction and supportive care. Despite the potential, current evidence is preliminary, with a paucity of randomized controlled trials, standardization challenges, and safety considerations. Future research should focus on rigorously evaluating Ayurvedic interventions in high-risk populations and developing protocolized integrative oncology models. Integrating Ayurvedic insights alongside conventional therapy may enhance prevention, reduce treatment-related side effects, and improve quality of life in CRC patients.